Tracked Changes. Multicore and symmetrical pair/quad cables for digital communications. Symmetrical single pair cables with transmission characteristics up to 1, 25 GHz. Horizontal floor wiring. Sectional specification Part 11, (1st June 2023) - British Standards Institution,
No abstract available